Analysis of Electronic Circuit Interference in Electrical Debugging Based on Computer-aided Software. Issue 3 (October 2020) - Xu, Shun
Abstract: In this paper, based on computer-aided software, the simulation method is used to explore the influence of the coupling voltage generated by the terminal load of the circuit board in the shielding body on the internal circuit from two aspects. When there is no through wire, the interference voltage is much smaller than that when there is no through wire. This shows that the anti-interference ability of the electronic circuit in the shield is reduced when there are through wires. When the vertical distance between the interference source and the line changes, the interference increases with the shortening of the distance; at the same time, affected by the working frequency of the interference source, the relative position symmetry interference is large at low frequency, and it increases with the relative position asymmetry at high frequency.